From Cape to Rafah, Jenin to Madagascar: Boycotting Israel at UWC - Palestine Solidarity Coalition (WritingThreeSixty, 2025)
The Palestine Solidarity Coalition at UWC (PSCUWC) emerged in late 2023 as an intergenerational mix of staff, students, workers, and alumni. The coalition operates alongside the Palestine Solidarity Association (PSA UWC), an SRC-affiliated student formation established at UWC in 2014. This short text and selection of images offers a brief, partial narrative on the movement(s) of the PSCUWC so far. Demands presented to the university management are reiterated and achievements of having resolutions ratified by UWC Council acknowledged. We outline a key motion presented to the UWC Senate on 28 May 2024, in which UWC passed a resolution on The Palestinian Campaign for the Academic and Cultural Boycott of Israel (or PACBI). There is also a message from the student executive of the PSA UWC. With the struggle for Palestinian liberation ongoing, the PSCUWC encourage WritingThreeSixty readers to get involved. Forward to a free decolonised Palestine!